Prognostic Value of Local Treatment in Prostate Cancer Patients With Different Metastatic Sites: A Population Based Retrospective Study - Jin, Shengming; Wei, Jiaming; Wang, Junjie; Wang, Beihe; Wu, Junlong; Gan, Hualei; Dai, Bo; Qin, Xiaojian; Lin, Guowen; Wei, Yu; Yang, Chen; Shen, Yijun; et al. (Frontiers in Oncology, 2020)
Our study aims to examine the impact of definitive local therapy in prostate cancer patients with different metastatic sites. A total of 5849 patients diagnosed with metastatic prostate cancer between 2010 and 2014 were identified from SEER database. Kaplan–Meier methods, log-rank analyses and multivariable Cox regression analysis was used to evaluate prognostic value of local treatment in patients with different metastatic sites. Survival curves and forest plots were also plotted to describe the prognostic value of definitive local therapy. In our study, 159 patients received radical prostatectomy and 62 received brachytherapy while 5628 did not receive local definitive local therapy. Survival analysis revealed that patients who received definitive local therapy had a better 5-year OS (P=0.011) and CSS (P=0.012). Multivariate analyses demonstrated that type of treatment was an independent prognostic factor for OS (P=0.011) and CSS (P=0.012), along with age at diagnosis, chemotherapy, PSA level and Gleason score. According to subgroup analysis, patients with bone metastasis or distant lymph nodes (LN) metastasis were significantly more likely to benefit from definitive local therapy. In addition, forest plots demonstrated that RP group had significantly favorable OS and CSS in subgroups of younger age at diagnosis, T2-3 stage, N0-1 stage, Gleason score=7 or ≥8, bone metastasis and distant LN metastasis. Our study suggested that local therapy improved survival in prostate cancer patients with bone or distant LN metastasis. Futhermore, patients who were at T2-3 stage or Gleason score≥7 also significantly benefit from definitive local therapy.